(untitled) (Theatrum historiae, 2011)
This study is an extended version of the paper presented at the 47th conference of German historiographers in Dresden in October 2008. This was a contribution to a longterm discussion of the association of the Bohemian Crown with the Holy Roman Empire. On the grounds of factual argumentation, the author confirms that the Bohemian Lands, whose affiliation to the Holy Roman Empire was clearly declared by the Golden Bull of 1356 issued by Charles IV, King of Bohemia and Emperor, did not become a part of the Holy Roman Empire of the German Nation, which was formed later and which symbolically began at the Imperial Diet in Worms in 1495. The Bohemian Lands were not declared a part of the Empire until 1708 in relation to the fact that the King of Bohemia newly became a member of the group of the Electors at the Imperial Diet. The King of Bohemia was also the king or emperor of the Roman Empire from 1531; however, this in no way influenced the relation between the Bohemian Lands and the Empire in the early Modern Period. It was not until the turn of the 17th and 18th centuries, when the Habsburgs’ diplomacy strove to enhance its influence among the Electors at the Imperial Diet (which was crowned with success in 1708), that we can see the special-purpose historical interpretation stating that the affiliation of the Bohemian Lands to the Empire had never been interrupted from the Middle Ages and the absence of the King of Bohemia at the Electors’ sessions was explained as a consequence of the fact the king also held the office of the emperor. The author uses concrete sources to demonstrate the process of gradual detachment of the Bohemian Lands from the Holy Roman Empire in the period from 1477 to 1495. Even, Maximilian I, Roman Emperor, found it more suitable to restore the newly formed Holy Roman Empire of the German Nation without the inclusion of the Bohemian Crown, for the unusually strong position which the King of Bohemia enjoyed within the medieval imperial hierarchy brought about instability within the empire. The exclusion of the Bohemia Crown from the empire took place under mutual consent and as a purely diplomatic event; therefore, it did not stir up any conflict of power (unlike in Switzerland). The author considers the resolution of the Bohemian Land Assembly of 1486 repealing the validity of the imperial legal regulations to be the key milestone of this process. The author also outlines three main areas enabling him to find exact proof that the Bohemian Crown did not form a part of the Empire: 1) The Bohemian Crown was not represented at the Imperial Diet from the moment this institution was formed (1495). Although the King of Bohemia retained the title of Prince-Elector, he was not a member of the Electors’ board. He never attended regular sessions of the Imperial Diet as the King of Bohemia before 1708. 2) The Bohemian Crown was not included in the system of Imperial Circles, it did not participate in the funding of the imperial armed forces, the imperial legal regulations were not effective in this area and the imperial judicial institutions did not deal with the affairs concerning the inhabitants of these lands. 3) Imperial taxes were never levied in the Bohemian Lands. The incorporation of the Bohemian Lands in the list of imperial tax payers of 1521 was only due to the fact that this tax assessment was prepared according to a list of medieval duties towards the emperor from a period when the Bohemian Lands were still a part of the empire. In the course of the 16th and 17th centuries, all political negotiations dealing with the issue of the association of the Bohemian Crown with the Empire witnessed both the Habsburgs (Emperor Charles I, Ferdinand I, the King of Bohemia and, later, Emperor) and the Bohemian Land Assembly clearly expressing that the Bohemian Crown was no longer a part of the Holy Empire. Contrary interpretation was only suggested by imperial estates, as they wished to enhance the budget of the imperial institutions with tax revenues from the Bohemian Lands.